From Italian domination in lexicographic product graphs to w-domination in graphs - Cabrera Martinez, Abel (Ars mathematica contemporanea, 2022)
R. Ehrenborg Ann. Comb. 18, No. 1, 75-81 (2014) noted that all tilings of a bipartite planar graph are encoded by its cubical matching complex and claimed that this complex is collapsible. We point out to an oversight in his proof and explain why these complexes can be the disjoint union of two or more collapsible complexes. We also prove that all links in these complexes are suspensions up to homotopy. Furthermore, we extend the definition of a cubical matching complex to planar graphs that are not necessarily bipartite, and show that these complexes are either contractible or a disjoint union of contractible complexes. For a simple connected region that can be tiled with dominoes ?$(2 × 1$? and ?$1 × 2)$? and ?$2 × 2$? squares, let ?$f_i$? denote the number of tilings with exactly ?$i$? squares. We prove that ?$f_0 - f_1 + f_2 - f_3 + … = 1$? (established by Ehrenborg loc. cit.) is the only linear relation for the numbers ?$f_i$?.
Keywords: Italian domination; italijanska dominacija; k-dominacija; k-domination; k-kratna dominacija; k-tuple domination; leksikografski produkt grafov; lexicographic product graph; w-dominacija; w-domination